Dampak Penggunaan Gadget terhadap Kemampuan Interaksi Anak Sekolah Dasar pada Situasi Pandemi Covid-19’ - Muhammad Iqbal Al Ulil Amri; Reza Syehma Bahtiar; Desi Eka Pratiwi (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
The purpose of this article is to examine the impact of the use of gadgets for elementary school children and their benefit in a pandemic situation gadget covid-19. The design of this study uses literature review. The steps in the literature review are (1). Topic search; (2). Specify a title; (3). Conclusions. Writing analysis techniques in writing literature review are; (1). data collection; (2). data reduction; (3). drawing conclusions. In this writing, there is an analysis in the form of negative and positive impacts. Impact: The children can interact with your friends wherever you are, you can learn online through in pandemic covid-19 negative impact children more often play a gadget play from a friend about the environment so that children become individualisticKeyword :Gadget, Interaction Social, Primary School Children, Covid-19 Pandemic,